A study on customized low degree of freedom hydraulics flexible material handling: Alternatives and limitations. Issue 1 (1st January 2017) - Priadythama, Ilham; Laksono, Pringgo Widyo
Abstract: Inventory plays very important role in a manufacturing system. Compare to conventional forklift vehicle, a robotic arm is more efficient and reliable because it requires no human operator. Unfortunately, a robotic system needs high investment and maintenance cost, commonly due to its control system as a consequence of its high Degree of Freedom (DOF). For medium enterprises it is still difficult to find high capacity but affordable system. Customized system with a hydraulic power pack is a considerable alternative solution since speed and accuracy is not a mandatory. Therefore, this paper provide a preliminary study report for a low DOF hydraulic robotic arm. Basically, this is a conceptual product development study. This research used the first 5 activity stages of Concept Development Phase from Generic Development Process. The first stage was Identifying Customer Needs which involved automation experts from academician. The second stage was Translating Customer Needs into Technical Requirement. The third stage was Generating Concept Alternatives which was more focused on mechanical structure alternatives. The fourth stage was Selecting The Best Concept which was based on valuation with some technical criteria. The final stage was Testing The Best Concept which addressed to evaluate its operational abilities by building a prototype. The development process produce three design alternatives which featured with only three DOF linkage system. A flexible material handling with PRR (Prismatic-Revolute-Revolute) robotic arm then selected as the best concept. The robotic arm was inspired by VANTA MD410ib/300 Palletizing Robot. The arm is actuated with a hydraulic cylinders for each DOF. The system was designed to handle material from or to a graded vertical shelf. A 450 mm sized prototype was build using small plastic hydraulics components. From several trial, we found a critical part on the second link actuator thus an additional counter balance or spring system should take in to consideration.